2019
DOI: 10.1186/s12983-019-0306-0
|View full text |Cite
|
Sign up to set email alerts
|

Parental incubation exchange in a territorial bird species involves sex-specific signalling

Abstract: BackgroundEffective communication between sexual partners is essential for successful reproduction. Avian parents with biparental incubation need to know how to negotiate, when and who will incubate, and how to harmonize partner exchange at the nest. Although considerable effort has been dedicated to studies of incubation rhythms, few studies have investigated how behavioural signals serve to tighten cooperation between parents. Moreover, existing studies are almost exclusively restricted to species in which l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In northern lapwings ( Vanellus vanellus ), exchange gaps were shorter when males relieved their calling female than when they relieved a non-calling female, and whenever a calling female left the nest for an incubation recess (i.e. no nest relief took place), her incubation recess was longer than when she left for the recess silently (Sládeček et al 2019). In zebra finches ( Taeniopygia guttata ), the calling rate of a returning male predicted the subsequent off-nest time of its female partner (Boucaud et al 2016a), while calling of an incubating female from inside the nest predicted whether or not the male relieved her from the nest (Boucaud et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In northern lapwings ( Vanellus vanellus ), exchange gaps were shorter when males relieved their calling female than when they relieved a non-calling female, and whenever a calling female left the nest for an incubation recess (i.e. no nest relief took place), her incubation recess was longer than when she left for the recess silently (Sládeček et al 2019). In zebra finches ( Taeniopygia guttata ), the calling rate of a returning male predicted the subsequent off-nest time of its female partner (Boucaud et al 2016a), while calling of an incubating female from inside the nest predicted whether or not the male relieved her from the nest (Boucaud et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas instantaneous coordination of incubation duties is possible in species where the off-duty parent (i.e. the one taking an incubation recess) stays near the nest (Smith et al 1978; Hawkins 1986; Glutz von Blotzheim 1999; Rodewald 2015; Sládeček et al 2019), such coordination is challenging in species where the off-duty parent forages or rests out of calling distance of the nest (Bulla et al 2015b). In some species, this can be hundreds or even thousands of kilometers away (Weimerskirch et al 1993; Weimerskirch 1995; González-Solís et al 2000; Boersma and Rebstock 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in birds have identified several factors that affect the (relative) contributions of the male and female parents in the ecological time scale, including the harshness of abiotic environments, especially temperature and rainfall [48][49][50][51], predation risk [52,53], the vulnerability of offspring in the absence of parental care [54,55], and the body condition of the parents themselves [56]. Studies also found that males and female can communicate and negotiate their parental effort [57][58][59][60][61], and the negotiation rules can be sex-specific [62]. Would those factors also play a role in driving sex roles evolution in different care forms in the evolutionary time scale?…”
Section: Parental Care Is Not a Unitary Trait Regarding Which Sex Provides Carementioning
confidence: 99%
“…Prior to departing from the nest, females, but not males, perform vocal displays which appear to signal the male. Female vocalizing increases the likelihood that the male will incubate and decreases the duration of the exchange gap ( Sládeček et al, 2019 ). Despite significant species differences in how incubation duties are shared, the range of ways birds coordinate activities using dynamic vocal exchanges at the nest remains striking.…”
Section: Behavioral Coordination and Biparental Care In Birdsmentioning
confidence: 99%